(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
The article highlights the formation, stages of development and specific features of the activities of educational centers in the Fergana region during the first thirty years of Uzbekistan’s independence (1991-2021). In the early years of independence, socio-political and economic changes, the increased demand for new knowledge and skills among the population and young people led to the emergence of non-state educational institutions, in particular, educational centers.